The economic burden of the ankylosing spondylitis in the Czech Republic: comparison between 2005 and 2008 - Petříková, Alena; Doležal, Tomáš; Klimeš, Jiří; Vocelka, Milan; Sedová, Liliana; Kolář, Jozef (Rheumatology international, 2013)
To investigate the burden of ankylosing spondylitis in the Czech Republic as a baseline for future health economic evaluations. Data were obtained from two cross-sectional studies Beda I (2005) and Beda II (2008), performed in 1,008 and 509 patients, respectively. Methodology used was Cost-of-Illness prevalence-based analysis bottom-up approach. Analysis was performed from payer (health insurance companies) and societal perspective (including productivity costs using friction cost approach). Mean age of sample in Beda I and Beda II was 50.2 and 52.5 years, male were present by 61.0 and 62.7 %; average disease duration was 23.0 and 26.4 years, respectively. Mean total annual costs per patient in the sample were €4,782 in Beda I and €5806 in Beda II. Average direct costs per patient in the sample per year are estimated at €1,812 (Beda I) and €2,588 (Beda II) with the average productivity costs €2,970 (Beda I) and €3,218 (Beda II). We observed a small decrement in percentage (6.7 %) of productivity costs for Beda II as an influence of higher consumption of biologic drugs, hence higher direct costs and possible productivity preservation. The largest direct cost burdens were spa procedures (45.3 %, Beda I) and biological drugs (52.8 %, Beda II). Unique analysis of the burden of the AS in the Central-Eastern Europe presents health care resource and cost consumption by comparing two cross-sectional prevalence-based studies. Further analysis should be carried to obtain data connecting health status with costs consumption in order to analyse the AS from this perspective.
Keywords: náklady na léky; Drug Costs; Cross-Sectional Studies; Prevalence; Balneology; balneologie; zdravotní pojištění; Time Factors; Sick Leave; Česká republika; ekonomické modely; Middle Aged; mužské pohlaví; prevalence; průřezové studie; Czech Republic; Health Care Costs; ankylózující spondylitida; Insurance, Health; zdravotnické zdroje; ženské pohlaví; Spondylitis, Ankylosing; výkonnost; pracovní neschopnost; Humans; časové faktory; Models, Economic; náklady na zdravotní péči; lidé středního věku; Efficiency; Health Resources; Female; absentérství; Absenteeism; lidé; Male